Design analysis of Experiments - Montgomery, Douglas C. (John Wiley and Sons, 2001)
This book offers a step-by-step guide to the experimental planning process and the ensuing analysis of normally distributed data. "Design and Analysis of Experiements" emphasizes the practical considerations governing the design of an experiment based on the objectives of the study and a solid statistical foundation for the analysis. Almost all data sets in the book have been obtained from real experiments. The book is accessible to all readers who have a good basic knowledge of expected values, confidence intervals, and hypothesis tests. It is ideal for use in the classroom at both the senior undergraduate and graduate level.